INTEGRIDADE TERRITORIAL, AUTODETERMINAÇÃO, SECESSÃO E RECONHECIMENTO: Francisco António de M. L. Ferreira de Almeida (De Legibus - Law Journal, 2021)
Te present article seeks to look upon the new dimensions of thePrinciple of Peoples self-determination in its internal and external aspects, especiallyto question whether a Right of Secession might be drawn upon them, which, exis-ting, directly compromises the fundaments of the Principle of Territorial Integrityof States, even in bordline cases and taking the form of remedy. At the end, its cons-trains and limitations are alluded to, in terms of exercise of international competen-ces, should there be no recognition by the newly formed territorial entity’s peers.